Nurse management and Preparedness for Disasters: A systematic Review - Rashed Sager AlHarbi, Hamad Mufarreh Alqahtani (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
This systematic review investigates peer-reviewed publications assessing nurses' readiness for disaster response.Background: With disasters occurring more frequently worldwide, nurses must adequately prepare to mitigate their adverse effects on affected populations. Despite increasing efforts to prepare nurses for disasters, evidence suggests they are often ill-prepared for effective response.Methods: A systematic review of scientific articles from 2006 to 2016 on nurses' disaster preparedness was conducted. SCOPUS, MEDLINE, PubMed, CINAHL, and PsychINFO were the primary databases used. Keywords included 'emergency,' 'disaster,' 'disaster preparedness,' 'disaster competencies,' 'disaster nursing,' 'disaster role,' and 'nurse.' Seventeen articles were selected.Findings: Previous disaster response experience and disaster-related training are key factors in increasing preparedness. However, many nurses feel insufficiently prepared and lack confidence in responding to disasters effectively.Conclusion: This review contributes to the understanding of disaster preparedness among nurses, with implications for academia, hospital administration, and nursing educators. The findings underscore the need for nurse educators and administrators to better equip nurses for disaster response.Implications for nursing and health policy: Hospitals should implement policies to address the lack of preparedness among nurses. Additionally, there is a need for further research and the provision of realistic disaster exercises to enhance nursing workforce preparedness